Characterization of T cell responses against Fusobacterium necrophorum naturally-induced foot rot in dairy cows - Yang, Yi; Zhang, Lulu; Yu, Chen; Zhang, Sheng; Ye, Chunmei; Yang, Zhangping; Zhang, Zhipeng (Frontiers in Immunology, 2026)
Bovine foot rot, an infectious disease caused by Fusobacterium necrophorum, leads to significant economic losses in the dairy farming. Research on bovine foot rot has primarily focused on the isolation and identification of the pathogen, as well as treatment methods. However, few studies have reported on the host’s immunological characteristics following infection. In this study, we employed an eight-color flow cytometry panel to characterize T-cell immune responses in dairy cows after infection by the F. necrophorum naturally-induced foot rot. We found that dairy cows with natural F. necrophorum-induced foot rot exhibited significantly increased percentages of NK cells, NKT cells, CD4+CD8- (helper) T cells, and CD4+CD8+ (double-positive) T cells compared to healthy cattle, while the proportion of WC1+ γδ T cells remained unchanged. However, the frequency of CD44High expressing cells was significantly elevated across all these T-cell subsets, suggesting their differential activation upon host infection with F. necrophorum. Compared with healthy cows, those with natural F. necrophorum-induced foot rot showed a significant increase in the percentages of effector memory T cells within NK and CD4+CD8+ T cell populations, and of central memory T cells within CD4+CD8+ and CD4+CD8- T cells, respectively. Our results, for the first time, revealed a potential role of CD4+CD8+ T cells and NK cells in the defense of F. necrophorum naturally-induced foot rot in cows.